2016
DOI: 10.1016/j.jpainsymman.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Exercise for Cancer-Related Fatigue in Patients With Lung Cancer Undergoing Chemotherapy: A Randomized Controlled Trial

Abstract: Tai Chi is an effective intervention for managing cancer-related fatigue in patients with lung cancer undergoing chemotherapy, especially for decreasing general fatigue and physical fatigue, and increasing vigor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 31 publications
3
117
1
Order By: Relevance
“…The interventions in the control group, which included conventional therapy [41, 44], low-impact exercise [42], sham Qigong [43], relaxation exercises [45], stretching and wellness education [46], sleep seminars [47], no intervention [48, 50], and fast walking [49], could be regarded as conventional treatment or relaxation exercise. Tables 1 and 2 provide detailed information on the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interventions in the control group, which included conventional therapy [41, 44], low-impact exercise [42], sham Qigong [43], relaxation exercises [45], stretching and wellness education [46], sleep seminars [47], no intervention [48, 50], and fast walking [49], could be regarded as conventional treatment or relaxation exercise. Tables 1 and 2 provide detailed information on the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [42, 4548] reported the random method of using a computer-generated random sequence, while one study [50] used only a random number table to divide communities into experimental community and control community. Two studies [41, 49] lacked descriptions of the method of random sequence generation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations